Strategi Meningkatkan Penghasilan untuk Kesejahteraan Keluarga Pedagang - Rahmad Hidayat; Topan Iskandar (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2022)
This article discusses the analysis of the strategies of hawkers in the cities of Tanjung Balai and Asahan, in a competitive market in increasing income. With regard to this research, in general, hawkers are junior high and elementary school graduates who have minimal knowledge of marketing strategies, but are able to survive the very strong competition for similar products. This research is a qualitative study through the figures and subjects that are used as roots in this study, a fruit seller including a number of informants who meet certain criteria. Collecting data in this study through interviews. The study aims to find out how hawkers start their business and how to market products.